Government and research Thirty Years of Evolution - Kogan, Maurice; Henkel, Mary.; Hanney, Steve; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
There has been a flare-up in interest in science policy and a key factor in this is the increased interest in analysing the role that research can play in informing policy making. A pioneering venture in this field was Government and Research: The Rothschild Experiment in a Government Department (1983) Heinemann. No other work had penetrated the deepest recesses of government to observe at first hand the attempts of a major department to determine its research agenda through collaboration with leading scientists in a wide range of fields, to observe how research was commissioned, and then evaluated by scientific teams, and how it began to enter the policy blood streams of the departments. This revised and augmented version updates the original text for current policy concerns and takes account of changes in science policy studies, whilst preserving its essential themes. It contains a succinct account of where matters now stand as well as an extended analysis of the themes that continue to dominate research and science policy. "Finally, the rest of the world has caught up with Kogan and Henkel. Twenty-five years ago their ground-breaking study of the UK's Department of Health led them to conclude that sustained interaction between scientists and bureaucrats was the key to unleashing the value of science for the policy process. I found the first edition of this book the single most compelling and comprehensive treatment of this complex interaction. They may have felt like voices in the wilderness then; today, however, they can take their rightful place as pre-cursors and leaders of what has become a mass-movement for 'evidence-based policy'. This re-issued and significantly updated edition, includes many recent initiatives that they and colleague Steve Hanney might rightfully claim as their offspring. The timeliness of the current edition only serves to highlight just how far ahead of their time they really were." Dr Jonathan Lomas, Chief Executive Officer of the Canadian Health Services Research Foundation.
Government and science -- Relationships between Government and Science -- Theories of Science and Science Policies -- Theories and Practice of Government -- The commissioning system in action -- The DHSS and the Research Management System -- Science and Macro Scientific Policy: the Case of the CSRC and the Intermediate Boards -- The Chief Scientist's Organisation and the Research Councils: the Case of the Panel on Medical Research and Relationships with the SSRC -- Research Liaison Groups and the Small Grants Committee: Two Contrasting Systems -- The Chief Scientist's Organisation and External Research Bases: the Case of the DHSS Research Units -- Review of Units and Scientific Merit: Chief Scientist's Visits -- Review of Units and Policy Relevance: the Customer Review -- Emerging processes and roles -- The Functions, Process and Impact of Research Commissioning -- Emerging Roles -- Policy after Rothschild and Generalisations.
Keywords: Science; Political science; Philosophy and science; Medicine; Social policy; Science; Science, general; Political Science; Philosophy of Science; Medicine/Public Health, general; Social Policy; Electronic books